Communicating at work : Principles and practices for business and the professions - Adler, Ronald B. (Boston McGraw Hill, 1992)
Contents: basics of business and professional communication, personal skills, working in groups, making effective presentations.
Includes bibliographical references and index
Keywords: Quản trị kinh doanh